Influence of Total Cattle, Milk Production, and Age of Cattle on Income of Dairy Farmers - Wibowo, Tabah Setyo; Faridatussalam, Sitti Retno (Research Horizon, 2025)
This study aims to analyze the factors that influence the income of dairy farmers in Boyolali Regency. Boyolali Regency is known as one of the largest milk-producing areas in Indonesia, so understanding the factors that influence farmers' income is crucial for improving the welfare of local farmers. The method used in this study is a quantitative approach with the SMART PLS analysis tool, which allows researchers to measure the relationships between variables in greater depth. Primary data were collected through questionnaires distributed to dairy farmers who participated in this study, while secondary data were obtained from relevant agencies such as the Central Statistics Agency (Badan Pusat Statistik/BPS) and the Ministry of Agriculture to support data validity. The variables studied include the number of livestock, milk production, and the age of livestock that produce milk. The results of the analysis show that these three variables have a positive and significant effect on farmers' income. With an R-squared value of 0.575, this research model explains 57.5% of the variance in farmers' income. These findings provide valuable insights for farmers and policymakers in designing the right strategies to increase income through more optimal livestock management, such as increasing the number of productive livestock and utilizing technology that supports milk productivity.